Molecular testing in stage I–III non-small cell lung cancer: Approaches and challenges. (December 2021) - Aggarwal, Charu; Bubendorf, Lukas; Cooper, Wendy A.; Illei, Peter; Borralho Nunes, Paula; Ong, Boon-Hean; Tsao, Ming-Sound; Yatabe, Yasushi; Kerr, Keith M.
Highlights: Routine molecular testing in stage I–III NSCLC has not been required to date. However, targeted agents are undergoing trials in adjuvant and neoadjuvant settings. Adjuvant osimertinib was recently approved for EGFR m (ex19del/L858R) resected NSCLC. Molecular testing in stage I–III NSCLC will be necessary in the near future. We discuss opportunities/challenges of integrating molecular testing into practice. Abstract: Precision medicine in non-small cell lung cancer (NSCLC) is a rapidly evolving area, with the development of targeted therapies for advanced disease and concomitant molecular testing to inform clinical decision-making. In contrast, routine molecular testing in stage I–III disease has not been required, where standard of care comprises surgery with or without adjuvant or neoadjuvant chemotherapy, or concurrent chemoradiotherapy for unresectable stage III disease, without the integration of targeted therapy. However, the phase 3 ADAURA trial has recently shown that the epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), osimertinib, reduces the risk of disease recurrence by 80% versus placebo in the adjuvant setting for patients with stage IB–IIIA EGFR mutation-positive NSCLC following complete tumor resection with or without adjuvant chemotherapy, according to physician and patient choice. Treatment with adjuvant osimertinib requires selection of patients based on the presence of an EGFR-TKI sensitizing mutation. Other targeted agents are currently being evaluated in the adjuvant and neoadjuvant settings. Approval of at least some of these other agents is highly likely in the coming years, bringing with it in parallel, a requirement for comprehensive molecular testing for stage I–III disease. In this review, we consider the implications of integrating molecular testing into practice when managing patients with stage I–III non-squamous NSCLC. We discuss best practices, approaches and challenges from pathology, surgical and oncology perspectives.